Comparative in vitro study of the shear bond strength of brackets bonded with restorative and orthodontic resins - Isber, Hassan; Ambrosio, Aldrieli Regina [UNESP]; Guedes Carvalhot, Paulo Eduardo; do Valle-Corotti, Karyna Martins; Siqueira, Danilo Furquim (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2011)
The aim of this study was to evaluate the shear bond strength of brackets bonded with different restorative systems and compare it with that afforded by an established orthodontic bonding system. Seventy human bicuspids were used, divided into five different groups with 14 teeth each. Whereas a specific orthodontic bonding resin (Transbond (TM) XT) was used in the control group, the restorative systems Charisma, Tetric Ceram, TPH Spectrum and Z100 were used in the other four groups. Seven days after bonding the brackets to the samples, shear forces were applied under pressure in a universal testing machine. The data collected was evaluated using the ANOVA test and, when a difference was identified, the Tukey test was applied. A 5% level of significance was adopted. The mean results of the shear bond strength tests were as follows: Group 1 (Charisma), 14.98 MPa; Group 2 (Tetric Ceram), 15.16 MPa; Group 3 (TPH), 17.70 MPa; Group 4 (Z100), 13.91 MPa; and Group 5 or control group (Transbond (TM) XT), 17.15 MPa. No statistically significant difference was found among the groups. It was concluded that all tested resins have sufficient bond strength to be recommended for bonding orthodontic brackets.
Keywords: Orthodontics; Shear Strength; Orthodontic Brackets; Dental Cements; Dental Bonding